2017
DOI: 10.1007/s00405-017-4740-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of sentinel lymph node biopsy for cT1/T2N0 tongue squamous cell carcinoma: a meta-analysis

Abstract: The aim of this study was to systematically evaluate the diagnostic value of the sentinel lymph node biopsy (SLNB) for cT1/T2N0 tongue squamous cell carcinoma (TSCC) patients. A comprehensive and systematic literature review was performed by searching the Embase and PubMed databases for English language articles published up to December 2016. The pooled overall sentinel lymph node (SLN) detection rate, sensitivity and negative predictive value (NPV) were used to evaluate the diagnostic value of SLNB which used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 52 publications
1
42
1
4
Order By: Relevance
“…Others have shown SLNB has no survival disadvantage in the T1 and T2 N0 OSCC group compared to SND. 2,11 There is some evidence to suggest SLNB in this setting may be associated with better functional outcomes and HRQoL than SND but evidence is weak. 12,13 It is possible that SLNB maintains the survival advantage of SND but retaining the HRQoL advantages of W&W. Neither assumption is yet certain.…”
Section: Introductionmentioning
confidence: 99%
“…Others have shown SLNB has no survival disadvantage in the T1 and T2 N0 OSCC group compared to SND. 2,11 There is some evidence to suggest SLNB in this setting may be associated with better functional outcomes and HRQoL than SND but evidence is weak. 12,13 It is possible that SLNB maintains the survival advantage of SND but retaining the HRQoL advantages of W&W. Neither assumption is yet certain.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond difficulties accepting new techniques, if the morbidity associated with elective supra-omohyoid selective neck dissection was considerable, oncologic head and neck surgeons would have had adopted SLNB readily. However, around half of the centers probably consider that convincing data of such superiority is lacking (30, 31). Probably the main advantage of SLNB is the more thorough pathologic examination of the lymph nodes most at risk, but the exact oncologic significance of micro-metastasis in HNSCC remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent meta-analysis of SLNB focusing exclusively on oral tongue cancers, including 35 studies (with 1084 patients) reported a pooled SLN detection rate, was 98% (95% CI 97%–100%). [22] The pooled overall sensitivity and NPV of SLNB were 0.92 (95% CI 0.88–0.95) and 0.96 (95% CI 0.94–0.97), respectively. The subgroup analyses demonstrated that studies that recruited a higher number of patients ( n = 30) were able to achieve a more stable NPV than the studies with a lower number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup analyses demonstrated that studies that recruited a higher number of patients ( n = 30) were able to achieve a more stable NPV than the studies with a lower number of patients. [22]…”
Section: Discussionmentioning
confidence: 99%